Perceived Barriers as Primary Determinant Factor in Uncleanliness and Unhealthy Behavior among Adolescents - Putri, Ronasari Mahaji; Devi, Hilda Mazarina; Parnawati, Tantry Ajeng (Universitas Tribhuwana Tunggadewi, 2024)
An increasing number of teenagers are engaging in uncleanliness and unhealthy behavior which is a significant cause for concern. These behaviors range from mild to severe. Clean and healthy living practice are far from the habits of teenagers. The aim of this study was to analyze the Health Belief Model in addressing the unhealthy behavior of adolescents in the Malang Region. The cross-sectional design used with a sample size of 148 individuals, selected through accidental sampling. Instruments included open and closed questionnaires as well as observational sheets, with data collection techniques comprising interviews and observations. Data analysis used univariate, bivariate and multivariate tests. The results indicated that three variables had a significant relationship with clean and healthy living behaviors: perceived barriers (p=0.000), perceived susceptibility (p=0.000) and perceived self-efficacy (p=0.009). The majority of respondents (63.5%) exhibited good clean and healthy living behaviors. The most dominant variable influencing a clean and healthy living was perceived barriers with OR=17.15. It is recommended that future researchers investigate the effectiveness of clean and healthy living behaviors education, also the dangers of smoking and sexual behavior in adolescents.